An analysis of Croatian political parties' pre-election manifestos and healthcare policies. (13th November 2019) - Ivankovic, D; Handanagic, S; Dzakula, A
Abstract: Background: Before the regular 2015 Parliamentary elections in Croatia, we identified and analysed topics and comprehensiveness of health policies (HPs) included in political parties' pre-election manifestos. After the loss of government confidence, we did a follow up before the 2016 preliminary elections. Here, we present a comparison of the 2015 and 2016 results. Methods: We used the Walt-Gilson policy model for the content analysis of pre-election HPs. Five evaluators independently reviewed manifestos for HPs through four dimensions: content, actors, processes and context. HPs proposed by at least two parties were included in the final analysis and by referring to any of four dimensions for specific HP, parties scored one point (maximum of four points per HP). Results: Seven out of the eight parties addressed healthcare topics in their manifestos, six discussed healthcare workforce and financing, while five discussed hospital systems, primary care, medical equipment and (re)organization of the healthcare. Parties earned 41% of all points for describing content, 28% for processes, 17% for actors and 14% for context of proposed HPs. Compared to the 2015 results, most comprehensively approached HPs changed to more focus on workforce and medical equipment. Topics of access to healthcare and people with disability earned significantly less points than in 2015. Conclusions: Parties' manifestos in both 2015 and 2016 focused on topics mostly represented in the public discourse on healthcare and daily media coverage. Financing the 2015 elections, as a consequence of a large financial restructuring effort of the hospital system at the time. Health workforce topped the 2016 elections, due to large emigration of health care professionals after legislative changes and Croatia's accession to the EU. Parties mostly focus on the content while they less frequently address the role of processes, actors, and the context needed for successful implementation of the recommended HPs.